Evaluating Biogenicity on the Geological Record With Synchrotron-Based Techniques - Callefo, Flavia; Maldanis, Lara; Teixeira, Verônica C.; Abans, Rodrigo Adrián de Oliveira; Monfredini, Thiago; Rodrigues, Fabio; Galante, Douglas (Frontiers in Microbiology, 2019)
The biogenicity problem of geological materials is one of the most challenging ones in the field of paleo and astrobiology. As one goes deeper in time, the traces of life become feeble and ambiguous, blending with the surrounding geology. Well-preserved metasedimentary rocks from the Archaean are relatively rare, and in very few cases contain structures resembling biological traces or fossils. These putative biosignatures have been studied for decades and many biogenicity criteria have been developed, but there is still no consensus for many of the proposed structures. Synchrotron-based techniques, especially on new generation sources, have the potential for contributing to this field of research, providing high sensitivity and resolution that can be advantageous for different scientific problems. Exploring the X-ray-matter physical interactions on a range of geological materials can provide insights on morphology, elemental composition, oxidation states, crystalline structure, magnetic properties, and others, which can measurably contribute to the investigation of biogenicity of putative biosignatures. Here we provide an overview of selected synchrotron-based techniques that have the potential to be applied in different types of questions on the study of biosignatures preserved in the geological record. The development of 3rd and recently 4th generation synchrotron sources will favor a deeper understanding of the earliest records of life on Earth and also bring up potential analytical approaches to be applied for the search of biosignatures in meteorites and samples returned from Mars in the near future.